Pengaruh Flash Sale dan Ulasan Online Terhadap Minat Beli Produk Alibaba di Indonesia - M. Wiranto; Irmanelly; Deka Veronica (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the influence of flash sales and online reviews on purchase intention for Alibaba products in Indonesia. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents. The data were analyzed using SmartPLS 4 to assess validity, reliability, and both direct and indirect relationships among the variables. The findings indicate that flash sales do not have a significant direct effect on purchase intention, while online reviews have a positive and significant effect. Furthermore, flash sales exert a significant indirect effect on purchase intention when mediated by AI-based product reviews. These findings suggest that integrating online product reviews can enhance the effectiveness of promotional strategies such as flash sales in stimulating consumer purchase intention.